Combining Foodscape and Touristscape: International Tourism Marketing for Singapore and Batam - Juliana, Juliana; Hubner, Ira Brunchilda; Indra, Febryola; Sianipar, Rosianna; Sitorus, Nova Bernedetta; Djakasaputra, Arifin (Jurnal Ilmiah Global Education, 2024)
The cities of Batam and Singapore are centers for tourist lovers, but official government authorities and destination marketing organizations tend to underestimate the potential of these destinations to be revisited by international tourists. In particular, there is little empirical research on international tourism, culinary tourism, and international marketing. This article aims to explore the scope of promotion of Batam and Singapore as culinary destinations. For the purpose of this research, A descriptive qualitative methodology using content analysis was developed to ascertain the relationship between food and tourism in the two places observed. using content analysis was developed to ascertain the relationship between food and tourism in the two observed places. The research method was carried out by conducting interviews and field observations. Data sources were obtained from interviews with Pokdarwis in Batam and tourists in Singapore. The research results stated the integration of Foodscape and Touristscape presents a promising avenue for international tourism marketing in both Singapore and Batam. These destinations possess rich culinary landscapes and diverse attractions that appeal to a wide range of travelers. By leveraging the synergy between Foodscape, which encompasses the culinary offerings reflective of their multicultural societies, and Touristscape, which includes the physical environment and attractions, Singapore and Batam can create compelling marketing strategies to attract international tourists. The combination of authentic culinary experiences, vibrant cultural attractions, and modern amenities positions both destinations as premier tourist destinations in the region.